177k views
1 vote
8 with an exponent of -8 multiplied by 8 with an exponent of 6

User Bunmi
by
5.9k points

1 Answer

5 votes

Answer:


8^(\left(-8* \:8\right)^6)=8^(64^6)

Explanation:

Given the expression


8^(\left(-8* \:8\right)^6)

Let the expression


8^(\left(-8* \:8\right)^6).....[A]

first solving


\left(-8* \:8\right)^6


\mathrm{Multiply\:the\:numbers:}\:8* \:8=64


=\left(-64\right)^6


\mathrm{Apply\:exponent\:rule}:\quad \left(-a\right)^n=a^n,\:\mathrm{if\:}n\mathrm{\:is\:even}


\left(-64\right)^6=64^6


=64^6

so expression [A] becomes


=8^(64^6)

Therefore,


  • 8^(\left(-8* \:8\right)^6)=8^(64^6)
User Ende Neu
by
6.8k points